Asian vs. European (Western) Management Style - the Position of Manager in Enterprise - Piasecka-Głuszak, Agnieszka (Azjatycki i europejski styl zarządzania - pozycja menedżera w przedsiębiorstwie, 2010)
This article aims to highlight the main aspects in the Asian management on the example of Japan and the European style of management. The author presents briefly definitions and types of managers, basic management styles used in the global economy and their characteristics, as well as methods of negotiation. In addition, the article presents the position manager takes in organization in the selected countries and what features he possesses.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 425-436
Keywords: management styles; European and Japanese style of management; manager; European manager; Asian manager; manager in enterprise